2017
DOI: 10.1590/0100-5405/2195
|View full text |Cite
|
Sign up to set email alerts
|

In vitro sensitivity of Corynespora cassiicola isolated from soybean to fungicides and field chemical control of target spot

Abstract: Soybean target spot (Corynespora cassiicola) has become an important disease in most soybean growing regions in Brazil. The sensitivity of 34 isolates of C. cassiicola to 11 fungicides was evaluated based on mycelial growth inhibition (boscalid, carbendazim, cyproconazole, fluopyram, fluxapyroxad, prothioconazole and thiophanate-methyl) or spore germination inhibition (azoxystrobin, picoxystrobin, pyraclostrobin and trifloxystrobin). In addition, the efficacy of five fungicides to control target spot was teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 16 publications
0
26
0
2
Order By: Relevance
“…The relatively low efficacy of CZM observed here could be attributed to the low fungitoxicity of the active ingredient itself or to the reported increased frequency of C. cassiicola isolates with resistance to this active ingredient in local populations of the pathogen (Teramoto et al ., ; Xavier et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low efficacy of CZM observed here could be attributed to the low fungitoxicity of the active ingredient itself or to the reported increased frequency of C. cassiicola isolates with resistance to this active ingredient in local populations of the pathogen (Teramoto et al ., ; Xavier et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Prosper et al (2018) [15] reported high level efficacy of pyraclostrobin and carbendazim against C. cassiicola in rubber. In another laboratory studies the fungicide pyraclostrobin was observed to be very promising in inhibiting the germination of the spores of C. cassiicola, the causal agent of target spot of soybean (Teramoto et al, 2017) [23] . The nursery studies on the evaluation of fungicides against corynespora leaf fall disease caused by C. cassiicolla revealed that the fungicides pyraclostrobin+ metiram thiophanate methyl, iprodione + carbendazim and mancozeb were effective in containing the disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to boscalid was found in cucumber C. cassiicola isolates in Japan (Miyamoto et al, 2009(Miyamoto et al, , 2010. HNS or resistant C. cassiicola isolates from Soya bean were reported in Brazil to fluxapyroxad and boscalid fungicides (Teramoto et al, 2017); and in China, the resistance of C. cassiicola isolates from cucumber to boscalid is widespread (Zhu et al, 2019).…”
Section: Benzimidazoles and Thiophanates Are Among Methyl Benzimidazolementioning
confidence: 99%